SPARKLE - Entrepreneurship for Sustainable Precision Agriculture - Vieri, Marco (Manuali - Scienze Tecnologiche, 2020)
SPARKLE - Entrepreneurship for Sustainable Precision Agriculture (SPA) is a course aiming to increase 'agripreneurship' among students, entrepreneurs and academics, enhancing knowledge and skills on technologies, innovations, entrepreneurial thinking and problem-solving skills into the farming sector. It also aims to transform the agricultural sector into a SPA-oriented system that could build an innovative ecosystem of agripreuners and agritechnicians around agriculture and entrepreneurship. The course is divided into four areas (SPA Overview, Tecnologies, Social and economic aspects and entrepreneurship in agriculture), 12 lessons and 55 topics leads students on a path for deepening the knowledge in a comprehensive system where technologies are a piece of the whole structure.